2015
DOI: 10.1177/1045389x15586448
|View full text |Cite
|
Sign up to set email alerts
|

Acoustical properties of magnetorheological fluids under applied magnetic field

Abstract: This work is devoted to the experimental study of acoustical properties of magnetorheological fluids subjected to magnetic field. Evaluation of the change in velocity of ultrasonic waves and attenuation coefficients in magnetorheological fluids based on synthetic oil and carbonyl iron versus magnitude and angle φ between wave vector and intensity direction of applied magnetic field has been carried out by pulse-phase method at 1.52 and 2.5 MHz. It was found that the anisotropy of attenuation coefficient was ~5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Zhu et al 368 investigated the conductivity of MREs under pressure while their acoustical properties have been recently tested by Hasheminejad and Shabanimotlagh 369 and by Korobko and coworkers. 370 Apart from a controllable storage modulus and loss factor, MREs also exhibit a change in shape when placed under a magnetic field. The field-active mode originates from the magnetostrictive behavior of MREs.…”
Section: Applicationsmentioning
confidence: 99%
“…Zhu et al 368 investigated the conductivity of MREs under pressure while their acoustical properties have been recently tested by Hasheminejad and Shabanimotlagh 369 and by Korobko and coworkers. 370 Apart from a controllable storage modulus and loss factor, MREs also exhibit a change in shape when placed under a magnetic field. The field-active mode originates from the magnetostrictive behavior of MREs.…”
Section: Applicationsmentioning
confidence: 99%
“…Rodríguez-López et al [ 18 , 19 ] analyzed the effects of uniformity, direction, and intensity of the magnetic field on the attenuation of ultrasonic elastic waves in MRF, and the results showed that the sound attenuation increased with an increase in the magnetic intensity until saturation was reached. Shen et al [ 20 ] and Baev et al [ 21 ] investigated the acoustic properties of MRFs in an applied magnetic field. Zielinski et al [ 22 ] and Muhazeli et al [ 23 ] investigated the acoustic absorption properties of foams coped with MRFs under magnetic fields, and found that the sound absorption frequency of the foams could be manipulated by varying the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, resonance phenomenon will occur when machining force frequency is close to natural frequency of the guideway system [7]. Magnetorheological (MR) fluid is a kind of controllable or smart fluid whose rheological properties can be dramatically and reversibly varied by the application of external magnetic field in milliseconds [8]. Therefore, it is suitable for real-time vibration control in hydrostatic guideways lubricated with MR fluids [9].…”
Section: Introductionmentioning
confidence: 99%
“…MR fluids are dispersions of micrometer-sized ferromagnetic particulates in an organic or aqueous carrier liquid, whose rheological behavior can be controlled by means of a magnetic field [8]. These fluids can exhibit changes in apparent viscosity of several orders of magnitude for applied magnetic flux densities of order of magnitude 1T [10].…”
Section: Introductionmentioning
confidence: 99%